Pengaruh Model Pembeljaran Think Pair Share (TPS) Terhadap Keterampilan Berpikir Kretif Mahasiswa Pada Mata Kuliah Pendekatan Pembelajaran - Paulina Maria Ekasari Wahyuningrum; Al Ikhlas; Yuliah Yuliah; Nur Sapta Riskiawati; Antonius Rino Vanchapo; M. Rusdi (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the Think Pair Share (TPS) learning model on students' creative thinking skills in the learning approach course. This research was conducted using a quasi-experimental research method by applying a 2 × 2 factorial design. The study population was STIPAS Tahasak Danum Pambelum students. The research sample consisted of 23 students in the experimental class and 24 students in the control class. Data collection was carried out using two kinds of instruments, namely the Group Embedded Figures Test (GEFT) instrument to measure students' cognitive styles and the instrument to test students' creative thinking skills in the form of essays. The results of data analysis and statistical tests show that there is an effect of the Think Pair Share (TPS) learning model on students' creative thinking skills in the learning approach course. Based on the results of this research, it is suggested to educators or lecturers, especially those who teach learning approach courses, to be able to apply the Think Pair Share (TPS) learning model developed as an innovation in the teaching and learning process.